Human Factors in Augmented Reality Environments - Huang, Weidong; Alem, Leila; Livingston, Mark A.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
None
Issues in human factors evaluations of augmented reality systems -- Human factors research in audio augmented reality -- Basic perception in head-worn augmented reality displays -- Pursuit of "X-ray Vision" for augmented reality -- Cognitive issues in mobile augmented reality: an embodied perspective -- Mobile augmented reality: a design perspective -- Design guidelines for mobile augmented reality - user experience -- Usability recommendations for mixed interactive systems: extraction and integration in a design process -- Concepts and subjective measures for evaluating user experience of mobile AR services -- Enhancing user roles in augmented reality interactive simulations -- Interactive AR installations: lessons learned in the field of art, design and cultural heritage.
Keywords: Computer science; Computer Communication Networks; Artificial intelligence; Computer vision; Telecommunication; Computer Science; User Interfaces and Human Computer Interaction; Artificial Intelligence (incl. Robotics).; Communications Engineering, Networks; Computer Imaging, Vision, Pattern Recognition and Graphics; Computer Communication Networks